2009
DOI: 10.1111/j.1365-2400.2009.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Riverine and early marine survival of stocked salmon smolts, Salmo salar L., descending the Testebo River, Sweden

Abstract: A combination of radio and acoustic telemetry was used to monitor the out-migration of hatcheryreared Atlantic salmon, Salmo salar L., in the River Testebo, its estuary and coastal system. As with many other Baltic rivers, the hydropower regulated River Testebo once had a self-sustaining salmon population that is now extinct. Substantial losses of smolts in the river (48-69%) and inner part of the estuary (43-47%) were found, but after leaving the estuary, the success of post-smolts moving out of the Bay was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 37 publications
6
31
0
Order By: Relevance
“…Managers should consider avoiding stocking locations upstream of such facilities until these poor passage efficiencies can be remediated. These results strengthen the suggestion that recovery through stocking is probably unattainable until such a time that the underlying causes responsible for the decline of the population are adequately addressed (Serrano et al , 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Managers should consider avoiding stocking locations upstream of such facilities until these poor passage efficiencies can be remediated. These results strengthen the suggestion that recovery through stocking is probably unattainable until such a time that the underlying causes responsible for the decline of the population are adequately addressed (Serrano et al , 2009).…”
Section: Discussionsupporting
confidence: 83%
“…osmoregulatory incompetence) cannot be ruled out. High estuarine predation is commonly reported in smolt migration studies (Hvidsten & Møkkelgjerd, ; Serrano et al ., ; Hedger et al ., ; Thorstad et al ., ). Reduced numbers of S. salar were detected within the array in 2014 despite this not being related to size.…”
Section: Discussionmentioning
confidence: 97%
“…As the smolts seem to prey upon naturally occurring objects in the drift and/or river bottom, it is unlikely that the prey availability is the reason for the observed variability in the amount of the empty stomachs. A possible explanation for the decreased feeding in the presence of an abundant food supply could be the elevated risk of predation during the inriver and estuary smolt migration (Jepsen et al 1998;Koed et al 2006;Serrano et al 2009b). Although there is a large variation in reported predation-induced mortality rates, several studies have found mortality to be as high as 50% or more (e.g.…”
Section: Discussionmentioning
confidence: 99%